Polypyrrole-conjugated zinc oxide nanoparticle as antiamoebic drugs against Acanthamoeba castellanii - Fitriya, Abu Mansur; Nanthini, Sridewi; Areeba, Anwar; Ayaz, Anwar *; Syed, Shahabuddin (Elsevier, 2022)
The presence of free-living amoebae that cause infections to the central nervous system, and cornea is one of the concerning health issues. Acanthamoeba spp. a genus of free-living amoebae can cause rare but deadly granulomatous amoebic encephalitis and blinding Acanthamoeba keratitis. Due to the limited and mostly ineffective treatment options against Acanthamoeba infections, new treatment modalities must be developed, such as use of nanotechnology for targeted therapeutics. Herein, this study was devised to test the amoebicidal effects of polymer conjugated with metal oxide nanoparticles against a clinical isolate of A. castellanii (T4). These nanoconjugates were synthesized and characterized by Field Emission Scanning Electron Microscope and Fourier Transform Infrared Spectroscopy. The amoebicidal assay was conducted to study the results of antiacanthamoebic action of Polypyrrole (PPy)-Zinc Oxide (ZnO). The results of antiacanthamoebic evaluation demonstrated that PPy-ZnO inhibited the viability of A. castellanii. Therefore, PPy-ZnO can be a potential drug candidate for the treatment of Acanthamoeba induced infections.